Examining the Role of Value Innovation on Competitive Advantage with Corporate Sustainability as Moderating Variable (Triple Bottom Approach) - Syafarudin, Afriapollo; Sihite, Mombang; Arrahman, Tharriq (Jurnal Doktor Manajemen (JDM), 2025)
This research aims to find the influence of value innovation on competitive advantage and its strengthened impact on corporate sustainability. The population in this study is building management manager who worked at office buildings in Jakarta. Research samples are based on purposive sampling method with a total of 500 data. Logistics regression analysis with MRA test with the strengthening corporate sustainability. The result showed that value innovation significantly affected competitive advantage. In addition, the results of this study also show that corporate sustainability strengthens competitive advantage.